The impact of economic equilibrium, globalization, human development, and market competitiveness on the sustainable development of manufacturing enterprises: The case of France, Germany, Italy and Poland - Magdalena Kowalska; Anna Misztal (Comparative Economic Research. Central and Eastern Europe, 2023)
The paper presents the results of an analysis of the impact of economic equilibrium, the Human Development Index, the KOF Globalization Index and the Global Competitiveness Index on the sustainable development of manufacturing enterprises and their components in France, Germany, Italy and Poland from 2008 to 2021. We use the Ordinary Least Squares (OLS) and the Seemingly Unrelated Regression methods (SUR). The results show that these external factors significantly impact an enterprise's sustainable development. Our models also show a different strength and direction of relationships between the explained and explanatory variables. Our models confirm the need to coordinate macroeconomics and environmental policy. It is important to use effective tools of economic support, and greater pressure from European Union institutions on countries that emit harmful substances is essential.
Keywords: 330; sustainable development; manufacturing enterprises; macroeconomic stabilization; globalization; market competitiveness